Perencanaan Peningkatan Perkerasan Kaku Dengan Menggunakan Metode Mdpj 2017, Pdt 14 2003, Dan Aastho 1993 Pada Jalan Pabean –Wadungasri, Sidoarjo - Ainiyah, Khoirotin; Hadi Putra, Kurnia (Rifa'Institute, 2023)
Highways are one of the means of land transportation needed by the community, so it is imperative to plan an effective pavement design (Panji, 2021). Apart from that, roads are also a means of land transportation that is very much needed by the community, so that roadworthiness is an important factor in providing a sense of security and comfort in driving. The higher increase in traffic must be balanced with the availability of quality infrastructure, Risdiyanto (2014). The increase in the number of vehicles crossing the road has a major impact on road damage, if regular maintenance is not carried out. Therefore, supervision of improving the quality of road infrastructure is very necessary, considering the number of vehicles that pass through these roads greatly affects the quality of the road itself Wadungasri Road is a collector road that is used as infrastructure for the activities of the Wadungasri Village community, both for economic, social, cultural and educational activities. Based on data from the Siodarjo Regency Central Statistics Agency, the population of Medaeng Village from 2012 to 2021 is known to have increased. In 2012 the population of the village numbered 10,386 people and in 2021 there will be 13,351 people. The increasing population every year will cause an increase in traffic which results in congestion. In order to improve road comfort services, it is necessary to hold a planning and maintenance program so that the road can provide comfort until the design life. For the above problems, it is necessary to carry out a study of efficient improvements in terms of maintenance and durability up to the design life. Top some. the author's considerations are planning an increase in rigid pavement on the Wadung Asri road section. According to Sukirman (1999), rigid pavement is considered to have a level of durability that is in sync with the design life, and maintenance that is more affordable than other pavements. In this study the authors analyzed the comparison of cement concrete pavement calculations using the new pavement method, namely MDPJ 2017, Pd T-14 2003 and AASHTO 1993. So that the hope from this research is to obtain the thickness of the required or appropriate and economical pavement.